Status‐Seeking Through Disaster Relief: India and China’s Response to Turkey–Syria Earthquakes - Dhanasree Jayaram; Lina Gong; Manaswini Dahagam Srivatsav (Politics and Governance, 2025)
Disaster relief cooperation has emerged as an active area of status-seeking by major powers. In recent decades, India and China have increasingly leveraged their disaster management capabilities to project their power globally. Disaster relief cooperation can be viewed through the lenses of the logics of both appropriateness and consequences. As “non-Western” powers, they have conventionally been known to contest disaster relief norms perceived by them as Western. Simultaneously, they have varied status-seeking approaches, guided by distinct geopolitical equations and involving different actors. Against this background, the article analyses the patterns and drivers of India and China’s status-seeking behaviour through disaster relief cooperation using the frameworks of the logics of appropriateness and consequences, in the case of the 2023 Turkey–Syria earthquakes. It delineates the actors and capabilities involved in their overseas disaster relief activities as well as their implications. It also investigates the strategic and normative imperatives, and geopolitical considerations of their disaster relief cooperation. The article argues that the status-seeking behaviour of India and China through disaster relief cooperation with Turkey and Syria is guided by an interplay between the logic of appropriateness and the logic of consequences, based on their motivations, capacities, and distinct contexts of the recipient countries.